Cartilage framework reconstruction after resection of thyroid cartilage chondrosarcoma: A case report - Valeria Navach; Francesco Chu; Augusto Cattaneo; Stefano Zorzi; Daniele Scelsi; Mohssen Ansarin (Otolaryngology Case Reports, 2017)
Background: surgical treatment of laryngeal chondrosarcoma is extremely broad and varies according to the affected subsite. Cricoid cartilage is the most commonly affected subsite. Thyroid cartilage localization is less frequent and is considered more favourable but there is no general consensus about current best practice for treatment of this rare tumor. Case report: we discuss the successful case of a young patient with thyroid cartilage chondrosarcoma, treated with radical surgery and cartilaginous graft reconstruction taken from costal synchondrosis in order to preserve laryngeal function and structure. Results and conclusion: in our experience this procedure was perfectly adapted to laryngeal reconstruction, providing easy graft harvesting and fast revascularization, laryngeal function preservation, avoiding postoperative rehabilitation arising from surgical damage of the donor site.